2010
DOI: 10.1620/tjem.221.35
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Surfactant Protein A Gene Are Associated with the Susceptibility to Recurrent Urinary Tract Infection in Chinese Women

Abstract: Recurrent urinary tract infection (r-UTI) remains one of the common infections affecting adult female. Almost 27% of women developed a recurrent UTI within the 6 months (Foxman 1990) and nearly 50% of women developed a recurrence within the first year following the initial infection (Mabeck 1972). Clinical studies showed that only a fraction of r-UTI patients had obvious functional, anatomic and behavioral risk factors, which were considered to be strongly associated with an increased risk of r-UTI. Recently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…Previous studies have shown that SP-D expression is increased in the mouse reproductive tract (31) and rat prostate (32) infected with Chlamydia and E. coli, respectively. A recent report showed that the urine SP-D levels were decreased in patients with recurrent urinary tract infection compared with healthy individuals (29). Taken together with the results obtained from this study and previous studies (29,31,32), the endogenous lectin SP-D possesses potential functions to protect against the bacterial infection.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Previous studies have shown that SP-D expression is increased in the mouse reproductive tract (31) and rat prostate (32) infected with Chlamydia and E. coli, respectively. A recent report showed that the urine SP-D levels were decreased in patients with recurrent urinary tract infection compared with healthy individuals (29). Taken together with the results obtained from this study and previous studies (29,31,32), the endogenous lectin SP-D possesses potential functions to protect against the bacterial infection.…”
Section: Discussionsupporting
confidence: 87%
“…A recent report showed that the urine SP-D levels were decreased in patients with recurrent urinary tract infection compared with healthy individuals (29). Taken together with the results obtained from this study and previous studies (29,31,32), the endogenous lectin SP-D possesses potential functions to protect against the bacterial infection. We investigated the protective role of SP-D in adherence of UPEC to the bladder urothelium, which is the first critical step for establishing UPEC infection, and examined the mechanisms of SP-D-dependent defense against UPEC infection.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…SP-D may also play a protective role against tubulointerstitial fibrosis (the common pathway to end-stage renal disease), as overexpressing SP-D in human kidney proximal tubular cells inhibits the expression of monocyte chemoattractant protein-1, a protein that when upregulated leads to disease progression [40] . In a study involving Chinese women, it was found that individuals carrying an Ala19Val polymorphism in SP-A1 or a Lys223Gln polymorphism in SP-A2 show increased susceptibility to recurring urinary tract infections [41] further emphasising that SPs seem to have important roles in preventing infection of the urinary tract.…”
Section: The Urinary Tractmentioning
confidence: 99%